The role of core self-evaluations in explaining depression and work engagement among managers - Hentrich, Stephan; Zimber, Andreas; Sosnowsky-Waschek, Nadia; Gregersen, Sabine; Petermann, Franz (Current psychology, 2017)
The present study tests interaction effects between working characteristics and core self-evaluations (CSE) among managers. Based on the job demands-resources model, we outline that CSE is a buffer for negative health-related consequences initialized by facing high job demands. Moreover, we hypothesize that CSE is positively linked to job resources and motivation. A sample of 282 managers participated in the study in Germany. Results based on hierarchical regression analysis confirmed that high CSE significantly weakens the positive relationship between high job demands and depression among managers. Furthermore, a significant interaction effect between job resources and CSE on work engagement was found. Therefore, the study reveals that it seems unlikely that CSE biases how managers appraise the environment since individuals low in CSE benefitted more from favorable working conditions than those high in CSE. Suggestions for future research as well as implications for theory and practice are derived.